(untitled) (The Conference Hub, 2025)
The article examines the essence of sustainable certification as a tool for environmental, social and economic responsibility. It provides an analysis of international and national standards such as FSC, Fair Trade, ISO 14001, etc. The role of sustainable certification in promoting the principles of sustainable development and the formation of responsible consumption is noted.